Health perceptions of elderly people aged over 65 age - Yigitbas, Cagla; Deveci, Suleyman Erhan (Cukurova Univ, Fac Medicine, 2019)
Purpose: The study was conducted to reveal the health perceptions of the elderly people aged over 65 living at home according to some of their demographic qualities. Materials and Methods: The study is a cross-sectional one with a population of 4158 people. 437 elderly people were included in the sample after calculations. The dependent variables of the research consist of the questions to measure the health perception and health-seeking behaviour of the participants while the independent variables consist of the socio-demographic qualities. Results: There was no difference between the general health perception and the age of the elderly people, the place where they spend most of their lives, social security status, number of children, hospitalized treatment in any health institution for the last one year, and any exposure to violence throughout one's life. Conclusion: The health perceptions of the elderly people were found to be negative according to some of their socio-demographical qualities.
Keywords: Living at home; elderly people aged over 65; health perception